Managing lean success : a warehouse balancing act. A - Yue, Tao, active 2022; Sherwood, Deborah (London : Rotterdam School of Management, Erasmus University, 2020)
In 2014 CEVA Logistics won a tender to provide third-party logistics (3PL) services to Uniqlo, a major Japanese fashion chain. CEVA’s lean management principles had been a selling point in helping CEVA to win the contract. Uniqlo quickly became one of CEVA’s largest customers. In the warehouse, volumes shot up soon after go-live. As management raced to keep up, constantly adjusting work floor procedures, lean principles and sustainability provisions were put on hold. A few months into the contract, employee morale was at a low and safety standards were being threatened. The project team realised that the continual switching of procedures was the source of confusion and unrest and decided that it was important to pick one and stick with it. This approach succeeded in returning clarity and regularity to the shop floor, and CEVA survived the winter high season. CEVA’s region manager was relieved and pleased. However, when Uniqlo’s CEO made a special trip from Japan to see operations in person, he was disappointed. CEVA needed to determine what had gone wrong and why. It needed to make a new plan, and fast.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lean manufacturing -- Management -- Case studies; Business logistics -- Case studies; Industrial management -- Case studies